P099 Invasive listeriosis in patients with immune-mediated inflammatory diseases on biologics and targeted therapies - a review of the literature. (23rd April 2022) - Allen, Victoria; Alveyn, Edward; Galloway, James
Abstract: Background/Aims: Listeria monocytogenes is a gram-positive bacterium found ubiquitously in the environment. Human infection is relatively rare and usually occurs after consumption of contaminated food. L. monocytogenes can cause an uncomplicated gastroenteritis in the immunocompetent. Vulnerable individuals are at risk of invasive disease. These include the elderly, pregnant women, neonates and people with impaired immunity, including those treated with biologics and targeted therapies for immune-mediated inflammatory diseases (IMIDs). Invasive listeriosis typically causes bacteraemia, meningoencephalitis and maternal-neonatal infection. Other reviews have described an association between TNF-alpha inhibitors and invasive listeriosis, however the impact of newer biologics and the JAK-inhibitors has not been described. Methods: The literature was systemically reviewed to assess the incidence of invasive listeriosis in patients with IMIDs treated with biologics or targeted therapies using Ovid Medline, EMBASE and the Cochrane Database of Systematic Reviews. Papers including patients over 16 years of age with rheumatoid arthritis (RA), ankylosing spondylitis (AS), axial spondyloarthritis, psoriatic arthritis, psoriasis, inflammatory bowel disease (IBD), (ulcerative colitis or Crohn's disease), managed with biologics or targeted therapies were included. Abstracts, case reports, case series, cohort studies, registry studies, randomised controlled trials and meta-analyses were included. Reports not published in English or not detailing the name of the biologic or targeted therapy used were excluded. The primary outcome was incidence of invasive listeriosis defined as isolation of L. monocytogenes from a normally sterile site. Results: Thirty-eight case reports, three disease-specific registry analyses, two randomised controlled trials and one meta-analysis were included in the final results. Together these studies reported 75 cases of invasive listeriosis in patients with IMIDs on biologics and targeted therapies. Seventy cases were described in patients treated with TNF-alpha inhibitors (49 with infliximab, nine with adalimumab, one with certolizumab pegol, one with golimumab and ten with etanercept). Two cases were described in patients treated with IL-12/IL-23 inhibitors (one with ustekinumab and one with guselkumab), one case was described in a patient treated with a gut-selective integrin antagonist (vedolizumab), one case in a patient treated with tocilizumab (an IL-6 inhibitor) and one case in a patient treated with a JAK-inhibitor (tofacitinib). Thirty-four patients had RA, 31 had IBD, five had psoriatic arthritis, two had ankylosing spondylitis, one had both psoriasis and psoriatic arthritis, one had psoriasis and another an unknown IMID. The reporting of listeriosis cases with TNF-alpha inhibitors has remained fairly steady over time so this association is not purely an early reporting phenomenon. Conclusion: Cases of invasive listeriosis have been reported across a range of different IMIDs, most often in patients with RA and IBD. Invasive listeriosis is not unique to patients treated with TNF-alpha inhibitors. The association between invasive listeriosis and other targeted therapies (e.g. IL-23 inhibition) needs further study. Disclosure: V. Allen: None. E. Alveyn: None. J. Galloway: Honoraria; AbbVie, Celgene, Chugai, Gilead, Janssen, Eli Lilly, Pfizer, Roche and UCB.